Identification of barriers to physical activity engagement in adolescents: A scoping review - Septiani, Riswanti; Istianah, Istianah; Sabila, Misna Zakiyus; Fauziyyah, Jihan Nafisah (PT WIM Solusi Prima, 2025)
This study aims to identify and map various barrier factors reported in the scientific literature related to the involvement of adolescents (aged 10-19 years) in physical activity. This scoping review method was conducted according to the PRISMA-ScR guidelines. A systematic search was conducted in electronic databases such as PubMed, Scopus, Web of Science, CINAHL, PsycINFO, and SPORT Discus, using relevant keywords about adolescents, physical activity, and barriers. Studies that identified barriers to AF in adolescents were included. Data were extracted and synthesized narratively and thematically to identify key categories of barriers. Results are a synthesis of 12 included studies identifying multidimensional barriers that fall into three main categories: (1) Individual/Personal: Lack of motivation, personal preferences, time constraints, self-confidence, and mental health issues. (2) Social/Interpersonal: Lack of family/peer support, parental objections, and group dynamics that influence acceptance. (3) Environmental/Structural/Policy: Lack of access to or quality of facilities, safety concerns in public spaces, cost and transportation constraints, and unsupportive school/community policies. The COVID-19 pandemic was also a significant barrier. In conclusion, barriers to physical activity in adolescents are complex and interrelated, requiring a holistic and multi-component approach. Addressing these barriers requires tailored interventions, support from multiple stakeholders (individuals, families, schools, communities), and innovation in promotion strategies, including digital solutions. Further research is needed to test the effectiveness of interventions targeting these specific barriers.